Force-Induced Nitric Oxide Promotes Osteogenic Activity during Orthodontic Tooth Movement in Mice. (6th September 2022) - Sun, Yuqing; Fu, Jingfei; Lin, Feiran; Li, Shengnan; Du, Juan; Liu, Yi; Bai, Yuxing
Abstract : Objectives . The aim of this study was to investigate the effect of nitric oxide (NO) on orthodontic tooth movement and the regulatory effect on bone formation. Design . A mouse orthodontic tooth movement model was established to measure the level of releasing NO. Besides, orthodontic tooth movement distance and the bone formation in the tension side of the orthodontic tooth were also analyzed. In vitro, human periodontal ligament stem cells (hPDLSCs) were cultured under tensile force stimulation. The production of NO and the expression level of nitric oxide synthase (NOS) were detected after mechanical stimulation. Furthermore, the downstream cellular signaling pathway regulated by NO was also explored. Results . The generation of NO steadily increased throughout the orthodontic tooth movement in mice. Orthodontic tooth movement was decreased in the NOS inhibitor group while it was accelerated in the NO precursor group. Force-induced NO promoted the osteogenic differentiation of human hPDLSCs under tensile force stimulation. And force-induced NO in hPDLSCs regulated the PI3K/Akt/ β -catenin signal pathway. Conclusion . NO is involved in the regulation of orthodontic tooth movement and promotes bone formation on the tension side of the orthodontic tooth. The PI3K/Akt/ β -catenin pathway is one of the downstream cell signal transduction pathways of NO in the orthodontic process.